A component-based framework for certification of components in a cloud of HPC services - de Oliveira Dantas, Allberson Bruno (2020)
HPC Shelfis a proposal of a cloud computing platform to provide component-oriented services for High Performance Computing (HPC) applications. This paper presents a Verification-as-a-Service (VaaS) framework for component certification onHPC Shelf. Certification is aimed at providing higher confidence that components of parallel computing systems ofHPC Shelfbehave as expected according to one or more requirements expressed in their contracts. To this end, new abstractions are introduced, starting with certifier components. They are designed to inspect other components and verify them for different types of functional, non-functional and behavioral requirements. The certification framework is naturally based on parallel computing techniques to speed up verification tasks.